Effect of polypharmacy on healthcare costs in hospitalized patients diagnosed with hypertension and diabetes mellitus in a tertiary care teaching hospital - Ravindra B. Nagarajappa; Ankitha Mahesha; Balaji S. Manjunath (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Hospitalised patients with diabetes mellitus and hypertension, particularly older adults, often have multiple comorbidities requiring polypharmacy. While the clinical consequences of polypharmacy are well documented, its economic impact, including healthcare expenditure, financial burden, and cost-related medication nonadherence, remains underexplored in resource-limited settings. Objectives of the study were to evaluate the association of polypharmacy and comorbidities with healthcare costs, financial burden, and cost-related medication non-adherence among hospitalised patients with diabetes mellitus and hypertension. Methods: A cross-sectional study was conducted among 180 hospitalised patients with diabetes mellitus and hypertension, with or without comorbidities, at a tertiary care teaching hospital. Data were collected using a validated proforma through patient interviews and medical records. Polypharmacy was defined as the use of ≥6 medications. Healthcare costs were categorized into direct medical, direct non-medical and indirect costs. Financial burden was estimated by comparing healthcare expenditure to income and cost-related medication nonadherence was assessed using a structured questionnaire. Statistical significance was set at p